Credit Risk Management: Exploring Current Practices and Important Elements in Business Financing Decisions - Siti Nor Amira Mohamad; Mohamad Yazis Ali Basah; Muhammad Ridhwan Ab. Aziz (Human Resource Management Academic Research Society, 2024)
Vol. 8, No. 5, May 2018, Pg. 548 - 562